Analisis Kemampuan Ruang Terbuka Hijau (RTH) Publik Dalam Menyerap Emisi Karbon Dioksida (CO2) Dari Kegiatan Transportasi Di Kecamatan Siak Hulu Dan Kecamatan Tambang Sebagai Wilayah Penyangga Kota Pekanbaru - Harlen Yosep Sitinjak; Muhammad Reza; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Carbon dioxide (CO2) emissions from transportation activities are the highest contributors to air pollution as much as 85%. One of the most implementative efforts to minimize the impact of global warming is through the provision of green open space. The purpose of this research is the value of carbon dioxide emissions from the number of motorized vehicles year as well as the value of the ability to absorb public green open space on CO2 emissions from transportation activities in Siak Hulu Sub-district and Tambang Sub-district. The method used in this research is recording traffic activities to calculate CO2 emissions values and calculating all public green space based on the number of protective trees that have a diameter of 20 cm, vegetation cover, and calculating the percentage of absorption capacity of public green open space. The results of the research obtained, CO2 emissions from amounting of motorized vehicles in Siak Hulu Subdistrict amounting to 81,413.03 tons CO2/year and in Tambang Sub-district amounting to 121,120.89 tons CO2/ year. The results of the analysis show that the existing public green open space in Siak Hulu Sub-district with a percentage of 1,67% and the Tambang Sub-district with a percentage of 1,13% hasn’t fulfilled the absorption of CO2 emissions from transportation activities. Keywords: Carbon Dioxide Emissions, Greenhouse Gases, Green Open Space